Modeling of Yield Loss in Potato Early Dying Caused by Pratylenchus penetrans and Verticillium dahliae - Wheeler, T A (Journal of nematology, 1992)
Yield-loss models were developed for potato early dying, caused by an interaction between Verticillium dahliae and Pratylenchus penetrans. Yield data were collected over 5 years (1985-1989) from potato plants grown in microplots infested with V. dahliae and (or) P. penetrans. The model y = b + (1 - b)/(1 + [VD/36.7]), where y was the relative yield (with uninfested controls = 1.0) and VD was the preplant density of V. dahliae microsclerotia per cm(3) soil, was fitted to the data set. When P. penetrans = 0, b = 0.55 (SE = 0.099), and when P. penetrans > 0, b = 0.23 (SE = 0.035). This model assumed that yield loss was proportional to the concentration of preplant microsclerotia of V. dahliae, and only qualitatively related to presence or absence of P. penetrans. This study contrasts with previous reports that predict yield loss being proportional to preplant population densities of both P. penetrans and V. dahliae